Ouvertures. - Guichard, Éric (Études Digitales, 2020)
The article repots that digital literates computerization and development of free graphic formats dedicated to the web with the refinement of the JavaScript programming language and the popularization of tools allowing the transition from one projection system. Topics include remarks valid for visualization as for graphics of scribal form as attested since the first computers; and opposition between literature and science, culture and humanism are the privilege of the first group.